A preliminary study on in vitro culture of musa sapientum cv. "Mundo" shoot tip. - Tirazona, Cathleen Benablo
The in vitro culture of Musa sapientum cv. `Mundo' has long been and widely practised using the modified Murashige and Skoog (MS) medium. However, it has been found out that certain modifications have been made specifically for each `Lakatan' and `Saba' cultivar for instance. The objectives of this study are to determine the individual effect of the MS media for `Lakatan' and `Saba' on the extent of development of the `Mundo' shoot tip cultures and to identify which medium tested shows better development of Musa sapientum cv. `Mundo' cultured in vitro., The results of this experiment show that the `Mundo' cultures are able to grow and develop in both media . However, the extent of development exhibited by the cultures is higher in the MS medium for `Lakatan' than the other one for `Saba'. It is concluded that, although `Mundo' cultivar grows and develops in both modified in vitro culture media, it cannot be well-propagated by using either of the two said media because of its slow and not so vigorous growth responses. Indeed, each cultivar has its own specific MS medium modifications for in vitro propagation. It implies, then that another modifications should be made specifically for the in vitro culture of Musa sapientum cv. `Mundo'.